2012
DOI: 10.1177/0192512112455443
|View full text |Cite
|
Sign up to set email alerts
|

The new right and the welfare state: The electoral relevance of welfare chauvinism and welfare populism in the Netherlands

Abstract: Next to their well-documented authoritarian cultural agenda, new-rightist populist parties have developed specific views on the welfare state: welfare chauvinism and welfare populism. This article studies the electoral relevance of these views for Dutch new-rightist populist parties by means of survey data representative of the Dutch population ( N = 1972). The electorate of those parties shows high levels of both welfare chauvinism and welfare populism. However, only welfare populism underlies support for new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(144 citation statements)
references
References 45 publications
6
127
1
3
Order By: Relevance
“…It remains committed also to stigmatizing social welfare 'dependency' (assistanat) and benefit fraud 12 . Recent research suggests that economic egalitarianism and support for the welfare state may in fact form two distinct independent ideological dimensions, and that both are represented in the ideology of the PRR (Achterberg et al, 2011;De Koster et al, 2013). Neoliberal and welfare populist policies are core ideological features of the French radical right, therefore less amenable to change.…”
Section: Empirical Results: a New Economic Profile For The Fn?mentioning
confidence: 99%
“…It remains committed also to stigmatizing social welfare 'dependency' (assistanat) and benefit fraud 12 . Recent research suggests that economic egalitarianism and support for the welfare state may in fact form two distinct independent ideological dimensions, and that both are represented in the ideology of the PRR (Achterberg et al, 2011;De Koster et al, 2013). Neoliberal and welfare populist policies are core ideological features of the French radical right, therefore less amenable to change.…”
Section: Empirical Results: a New Economic Profile For The Fn?mentioning
confidence: 99%
“…Their label, "welfare chauvinism", has become the standard term for the opinion that immigrants are less entitled to welfare benefits and services than the native population (cf. Van der Waal et al 2010;Mewes and Mau 2012;Reeskens and Van Oorschot 2012;De Koster et al 2013). 1 In the light of Larsen's formulation of institutional theory, this raises the question of whether three worlds of welfare chauvinism can be distinguished: are the native populations of liberal welfare states most reluctant to distribute welfare benefits and services to immigrants, followed by natives living in conservative welfare states, while those living under social-democratic regimes are most willing to do so?…”
Section: Introductionmentioning
confidence: 99%
“…de Koster et al 2013). One could argue that new-rightist parties do not compete electorally with new-leftist parties: their respective ideologies are very different, suggesting that they do not compete for the same group of voters.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…And indeed, research has consistently demonstrated that openness towards cultural diversity (shorthand: libertarianism) underlies a vote for the new left (Achterberg and Houtman 2006;Houtman and Achterberg 2010), while support for new-rightist parties is largely rooted in discontent about immigration and ethnic diversity (shorthand: authoritarianism) (de Koster et al 2013;Houtman et al 2008;Ivarsflaten 2008;Rydgren 2008;van der Brug 2003). And this cleavage does not consist of unconnected individual issues, but represents one coherent value dimension, as has been found time and again from the 1950s onwards (for a recent empirical corroboration of these findings, see Elchardus and Spruyt 2012).…”
Section: Progressiveness and The New Rightmentioning
confidence: 99%